(untitled) (Journal of the College of Basic Education, 2022)
The current research aims to measure the effect of using an educational unit in the subject (decoration) to develop some skills in teaching art education for primary school teachers who have medium skills in specialized art education. Teaching art education, where the educational unit was limited to the skill of decoration. The researcher prepared a cognitive achievement test in the principles of decoration, in addition to an observation form for the skill performance . The research sample consisted of (34) teachers who were selected with medium experience in the skills of teaching art education. The results of the study showed that there were statistically significant differences between the scores of the experimental group in the pre and post application of the cognitive achievement test, which came in favor of the post test. In light of these results, the researcher concluded some recommendations for preparing similar educational units For teachers of art education with weak and medium experiences in all stages of study, with some proposals related to the variables of the current research.